Pelatihan Pengembangan Perangkat Pembelajaran Berbasis Kurikulum Merdeka melalui Model PjBL pada Guru MGMP SMA se-Kota Tasikmalaya - Apiati, Vepi; Heryani, Yeni; Hermanto, Redi; Muzdalipah, Ipah (LSM Catimore dan Sahabat, 2024)
Activities for implementing the Community Service Program Featured Study Program Scheme (PbM-PUPS) by the Mathematics Education Department towards the High School Mathematics MGMP which is implemented in the form of